Human motivation by some Cuban theorists - Luis Alfredo González Collera (Revista MENDIVE, 2010)
The current article offers a summary of the theories of three outstanding Cuban psychologists, whic h have contributed with important knowledge to the motivational sphere of personality. These theoretical approaches constitute the epistemology of base to new studies about motivation in any area of knowledge, although they have a special emphasis on the educative and pedagogic area as well as on the personal development.